Vernacular Architecture in México: The Blue Corn Research Center in Michoacán - Sindy Melissa Godínez De León; Ivana Edith Zapata Castañeda; Lucero Alejandra (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
In Mexico, a large part of the population is still engaged in primary activities such as agriculture. That is why government and academic institutions have focused on encouraging the improvement and optimization of the farming of basic grains through research and technology. This work aimed to propose a building based on the Mexican vernacular architecture of Michoacán using local materials. The architectural project used the scientific method of analyzing socio-economic indicators, territory, and cultural conditions. As a result, we got a building that promotes the increase in the production of blue corn and solves part of the student lag in the rural area of Michoacán. The building contemplates open access for people of the surrounding towns through community use. Its design applies passive thermal control strategies. The project is a connection between local agricultural customs and the field of research. Keywords: contemporary